PERILAKU MORAL PESERTA DIDIK KELAS V SD NEGERI BARUSARI 02 - Muhammad Falih Rifqi; Husni Wakhyudin; Mudzanatun (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Moral behavior has an important role in shaping the character and personality of individuals from an early age. Therefore, understanding and implementing good moral behavior in the learning environment is a crucial aspect in the development of students. This study aims to analyze moral behavior towards learning in fifth grade students at SD Negeri Barusari 02. The approach used in this research is descriptive qualitative with the research methods used are observation, questionnaires, interviews, and documentation as data collection instruments. The results of the study showed that fifth grade students at Barusari 02 Public Elementary School had positive moral behavior. Learning done in schools can have a positive impact on the moral behavior of students. Therefore, it is important to continue to apply learning that can help improve students' moral behavior, such as guiding positive moral behavior and introducing good moral values.